Accelerating the extracellular electron transfer of Shewanella oneidensis MR-1 by carbon dots: The role of carbon dots concentration. (20th July 2022) - Zhang, Peng; Yang, Chenhui; Li, Zeng; Liu, Jia; Xiao, Xiang; Li, Da; Chen, Chong; Yu, Miao; Feng, Yujie
Hightlights: Carbon dots enhance biofilm immobilization and flavins secretion of Shewanella . Integration of carbon dots and cytochromes strengthens electron transfer chains. Overload of CDs restricts the promotion effect on extracellular electron transfer. Abstract: The high performance of microbial extracellular electron transfer (EET) is essential for bioremediation and bioenergy generation. Carbon dots (CDs) modified electroactive microorganisms showed an increased electron transfer efficiency. However, the influence of CDs' concentration the EET has not been illustrated before. Herein, we reported that the addition of CDs increased the current generation by accelerating the EET process. The maximum current output of microbial electrochemical cells with the addition of CDs was increased by more than 5 times compared to pure Shewanella oneidensis MR-1. With CDs addition, the increase of biofilm immobilization and flavins secretion improved the direct and mediated EET process. Electrochemical analyses clarified that the combination of cytochrome c with CDs resulted in a faster electron transfer rate. The overload of CDs would restrict their promotion effect on EET, which may be due to their biotoxicity to bacteria. This work offered the insight of CDs' concentration on the efficiency of EET, not only promoting the related applications of EET but also inspiring the regulation of microorganism function via nanomaterial.